Assessment of SARS-CoV-2 tests costs and reimbursement tariffs readjustments during the COVID-19 pandemic (Swiss Medical Weekly, 2022)
INTRODUCTION: While laboratories have been facing limited supplies of reagents for diagnostic tests throughout the course of the COVID-19 pandemic, national and international health plans, as well as billing costs, have been constantly adjusted in order to optimize the use of resources. We aimed to assess the impact of SARS-CoV-2 test costs and reimbursement tariff adjustments on diagnostic strategies in Switzerland to determine the advantages and disadvantages of different costs and resource saving plans.MATERIALS AND METHODS: We specifically assessed the cost of diagnostic SARS-COV-2 RT-PCR using five different approaches: i) in-house platform, ii) cobas 6800® (Roche, Basel, Switzerland), iii) GeneXpert® SARS-CoV-2 test (Cepheid, Sunnyvale, CA, USA), iv) VIASURE SARS-CoV-2 (N1 + N2) Real-Time PCR Detection Kit for BD MAX™ (Becton Dickinson, Franklin Lake, NJ, USA), v) cobas® Liat® SARS-CoV-2 & Influenza A/B (Roche, Basel, Switzerland). We compared these costs to the evolution of the reimbursement tariffs.RESULTS: The cost of a single RT-PCR test varied greatly (as did the volume of tests performed), ranging from as high as 180 CHF per test at the beginning of the pandemic (February to April 2020) to as low as 82 CHF per test at the end of 2020. Depending on the time period within the pandemic, higher costs did not necessarily mean greater benefits for the laboratories. The costs of molecular reagents for rapid tests were higher than of those for classic RT-PCR platforms, but the rapid tests had reduced turnaround times (TATs), thus improving patient care and enabling more efficient implementation of isolation measures, as well as reducing the burden of possible nosocomial infections. At the same time, there were periods when the production or distribution of these reagents was insufficient, and only the use of several different molecular platforms allowed us to sustain the high number of tests requested.CONCLUSIONS: Cost-saving plans need to be thoroughly assessed and constantly adjusted according to the epidemiological situation, the clinical context and the national resources in order to always guarantee that the highest performing diagnostic solutions are available. Not all cost-saving strategies guarantee good analytical performance.